Caffeine ingestion compromises thermoregulation and does not improve cycling time to exhaustion in the heat amongst males - Jenny Peel (European Journal of Applied Physiology, 2024)
Purpose: Caffeine is a commonly used ergogenic aid for endurance events; however, its efficacy and safety have been questioned in hot environmental conditions. The aim of this study was to investigate the effects of acute caffeine supplementation on cycling time to exhaustion and thermoregulation in the heat. Methods: In a double-blind, randomised, cross-over trial, 12 healthy caffeine-habituated and unacclimatised males cycled to exhaustion in the heat (35 °C, 40% RH) at an intensity associated with the thermoneutral gas exchange threshold, on two separate occasions, 60 min after ingesting caffeine (5 mg/kg) or placebo (5 mg/kg). Results: There was no effect of caffeine supplementation on cycling time to exhaustion (caffeine; 28.5 ± 8.3 min vs. placebo; 29.9 ± 8.8 min, P = 0.251). Caffeine increased pulmonary oxygen uptake by 7.4% (P = 0.003), heat production by 7.9% (P = 0.004), whole-body sweat rate by 21% (P = 0.008), evaporative heat transfer by 16.5% (P = 0.006) and decreased estimated skin blood flow by 14.1% (P < 0.001) compared to placebo. Core temperature was higher by 0.6% (P = 0.013) but thermal comfort decreased by -18.3% (P = 0.040), in the caffeine condition, with no changes in rate of perceived exertion (P > 0.05). Conclusion: The greater heat production and storage, as indicated by a sustained increase in core temperature, corroborate previous research showing a thermogenic effect of caffeine ingestion. When exercising at the pre-determined gas exchange threshold in the heat, 5 mg/kg of caffeine did not provide a performance benefit and increased the thermal strain of participants.